Investigation of the apoptotic way induced by digallic acid in human lymphoblastoid TK6 cells - Bhouri, Wissem (BioMed Central, 2012)
BACKGROUND: The digallic acid (DGA) purified from Pistacia lentiscus. L fruits was investigated for its antiproliferative and apoptotic activities on human lymphoblastoid TK6 cells. METHODS: We attempt to characterize the apoptotic pathway activated by DGA. Apoptosis was detected by DNA fragmentation, PARP cleavage and by evaluating caspase activities. RESULTS: The inhibition of lymphoblastoid cell proliferation was noted from 8.5 μg/ml of DGA. The induction of apoptosis was confirmed by DNA fragmentation and PARP cleavage. We have demonstrated that DGA induces apoptosis by activating the caspase-8 extrinsic pathway. Caspase-3 was also activated in a dose dependent manner. CONCLUSION: In summary, DGA exhibited an apoptosis inductor effect in TK6 cells revealing thus its potential as a cancer-preventive agent.